“Dialectical Contradictions” in the Neoclassical Theory and Policy Regarding Market Competition: The Consumer and His Continuos Burden of Crisis - Octavian-Dragomir Jora; Gheorghe Hurduzeu; Mihaela Iacob; Georgiana-Camelia Crețan; Raluca-Elena Hurduzeu (Amfiteatru Economic)
In spite of the apparent general consensus, both economic theory in abstracto and the political practice in the realm of competition are looked upon from (too) many perspectives. Far from being convergent or even complementary, the “theories” and “policies” are rather contradictory and conflicting “in” and “between” them. Nominally subsumed to the “consumer welfare”, the praise of competition and of its disciplinary power within the market economy (and twistingly even within the socialist one) has experienced between the eras of “classical” and “neoclassical” economic science a subtle transition from the paradigm of “freedom” to that of “perfection”. And the transition was accomplished with a significant risk of loss both in internal consistency and realistic adequacy, which undergo the fictional methodology as well as the mathematical formalism, endemic in the neoclassical approach. The tension inside the theorizing of competition cohabits with the one inside the policies’ camp: the regulations often seem to be at odds with the stated commitment towards the consumers (seen holistically and aggregately). Some of the real “flesh and blood” consumers become in fact passive objects of “pro-competition” coercive rearrangements of welfare in three hypostases that individuals (though unevenly) subsume: as “consumers” (of goods and services), as “competitors” (factors of production in labour markets) and as “citizens” (asymmetrically hit by the myriad of policies). This paper offers an “original recovery” of a common sense argument: after the mainstream imposition of “perfect” instead of “free” competition standard, the neoclassicism-inspired public policies end up promoting a competition climate heavily strained from both freedom and perfection.